Training On Healthy Ways To Clean The Sense Of Touch (HANDS) For Children - Zulfakar; M. Zainal Mustamiin (YAYASAN HAMJAH DIHA bekerjasama dengan PENA INSTITUTE, 2022)
In human daily life in general, especially children, cleaning the sense of touch (hands) in a way that is not correct or does not meet health standards, this of course can result in a number of diseases for the child. From a number of aspects that can result in a child's lack of awareness to clean hands properly based on health standards, among others, are: a) lack of understanding of hygiene; b) lack of understanding of germs that cause disease; c) lack of understanding of diseases that can be caused by unclean hands. clean, in addition to the lack of awareness of the guardians of students in the AlKhairiyah Educational Institutions, Rajak, Sukaraja, East Praya, Central Lombok district, which is caused by factors of the social and economic status of their extended families, the majority of whom have income below the average standard. national average per month and domiciled in a very simple area or housing in the middle of a village. It is hoped that after participating in this training activity, educational participants are able to routinely maintain their hand hygiene by cleaning the health standards that have been described, so that the risks that may arise before participating in the training can be minimized or even eliminated, especially the spread of diseases caused by dirty hands at the time of the training. Enjoy their daily food at home, especially when they eat rice, which they routinely do based on the normal standard of three times a day and night.